Association of Fatigue With Sleep Duration and Bedtime During the Third Trimester - Ma, Duo; Kang, Yimin; Wang, Denglan; Chen, Haoxiong; Shan, Ligang; Song, Chun; Liu, Yanlong; Wang, Fan; Li, Hui (Frontiers in Psychiatry, 2022)
Purpose To investigate the association of fatigue and sleep habits of pregnant women to explore the effect of sleep duration and bedtime on fatigue during the third trimester. Methods A total of 465 Chinese Han pregnant women in the third trimester (after 28 weeks) with a singleton gestation were recruited. Sleep habits (including bedtime, sleep onset latency, and night sleep duration) and the 14-item Fatigue Scale (FS-14, used to assess fatigue) were collected. Results The effects of sleep duration and bedtime on FS-14 physical and total scores were significant. FS-14 physical scores and total scores of the participants in the group of sleep before 23 o’clock (SBC) of short sleep duration (< 7 hours) were significantly higher compared to the participants in the group of SBC of in normal sleep duration, and those of the participants in SBC of normal sleep duration were significantly lower than the participants in the group of sleep after 23 o’clock of normal sleep duration. There were negative correlations of sleep duration with FS-14 physical score and total score in SBC of short sleep duration. Conclusion Sleep less than 7 hour or bedtime after 23 o’clock was associated with increasing fatigue levels of pregnant women in the third trimester. Therefore, it is necessary to develop good sleep habits (enough sleep duration and early bedtime) to keep low-level fatigue for pregnant women in the third trimester.